PAYMENT CREDIT DATA PROCESSING SYSTEM JPS - Dwi Cahyasari; Eko Hadiyanto SSi, MM (Jurnal Sistem Informasi, 2002)
With the rapid development of technology especially in the field of computerization, it will bring influence to another field. As in the data processing system JPS credit payments using a computerized system then all the problems that arise such as the unavailability of credit payment data information is accurate and informative data that does not credit payments on time each month to be resolved.Â  With the computerized system at the data processing system JPS credit payments can give more meaning to LKMD due to the development of the new system may reduce the work less effective and efficient.